Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2): A Perspective Through the Lens of the Veterinary Diagnostic Laboratory - Stokol, Tracy; McAloose, Denise; Terio, Karen A.; Salguero, Francisco J. (Frontiers in Veterinary Science, 2020)
The SARS-CoV-2 pandemic has resulted in unprecedented challenges to veterinary diagnostic laboratories. These challenges include partial or complete shutdowns, interrupted courier services, disruptions in workflow and diagnostic testing, new physical distancing practices, protocol development or enhancement for handling samples from high-risk or susceptible species, and fulfilling requirements for pre-test permission approval from state and federal veterinary agencies, all of which have been implemented to prevent or minimize exposure and transmission of SARS-CoV-2 locally or regionally. As in people, SARS-CoV-2 infects animals through direct animal-to-animal contact and aerosol transmission between animals. Humans can also infect pets or other animals in their care and, although human-to-human transmission is the main route of viral spread in people, infected animals and specimens of their bodily fluids or tissues are a potential source of infection for veterinarians and technical or laboratory personnel that are handling them. In this perspective, we discuss how SARS-CoV-2 has necessitated rapid changes in laboratory operation to minimize zoonotic risk to personnel and to implement tests for identifying the virus in animals. The pandemic has highlighted the adaptability and quick response of veterinary diagnosticians to an emerging infectious disease and their critical role in maintaining animal health, while synergizing with and protecting human public health.